2012
DOI: 10.7853/kjvs.2012.35.4.343
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding the combination with Lactobacillus plantarum and Bacillus subtilis on fecal microflora and diarrhea incidence of Korean native calves

Abstract: This study was investigated the effects of feeding the combination with Lactobacillus plantarum and Bacillus subtilis on the diarrhea incidence and fecal microflora of weaned calves. A total of 12 newly weaned calves were allocated to two dietary treatments in a randomized design based on body weight. The dietary treatments included a commercial basal diet supplemented with: 1) no microbial inoculants (Control); 2) a mixture of Lactobacillus plantarum and Bacillus subtilis (LB). Calves were fed diets for a 4-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…They observed no improvement in faecal score of the MOS supplemented calves, but contrary to the present study Ghosh and Mehla () observed that there was lower faecal score in the calves supplemented with MOS (4 g/d) compared to the control calves. On probiotic supplementation, faecal scores and the duration of diarrhoea were significantly decreased ( p < .05) compared with the control group (Lee, Kang, Yu, Kim, & Lee, ). In this study, all the calves were provided with colostrum within the first 24 hr of birth, and it is an established fact that consumption of an adequate quantity of colostrum within the first 24 hr of birth provides acquired passive immunity (He et al., ), which is inversely correlated with morbidity and mortality of the calves (Meganck, Hoflack, & Opsomer, ).…”
Section: Discussionmentioning
confidence: 83%
“…They observed no improvement in faecal score of the MOS supplemented calves, but contrary to the present study Ghosh and Mehla () observed that there was lower faecal score in the calves supplemented with MOS (4 g/d) compared to the control calves. On probiotic supplementation, faecal scores and the duration of diarrhoea were significantly decreased ( p < .05) compared with the control group (Lee, Kang, Yu, Kim, & Lee, ). In this study, all the calves were provided with colostrum within the first 24 hr of birth, and it is an established fact that consumption of an adequate quantity of colostrum within the first 24 hr of birth provides acquired passive immunity (He et al., ), which is inversely correlated with morbidity and mortality of the calves (Meganck, Hoflack, & Opsomer, ).…”
Section: Discussionmentioning
confidence: 83%
“…In consonance with the present outcome, Bayatkoushar et al 58 reported that supplementation of lactic acid bacteria reduced fecal score, and pH as compared to the control group. Similarly, Lee et al 59 and Varada et al 21 revealed that probiotic supplementation substantially shortened ( p < 0.05) the duration of diarrhea and the fecal score in treated groups compared to the control group. Sahu et al 60 reported that the administration of probiotics and prebiotics significantly ( p < 0.05) improved fecal scores in Jersey crossbred calves.…”
Section: Resultsmentioning
confidence: 74%
“…However, contrary to the present findings, supplementation of probiotic significantly reduced (P < 0.05) faecal scores and duration of diarrhoea in treatment groups as compared to control groups, possibly due to the the surrounding environment. [43,44]. Consequently, the benefit from probiotic administration for the health of neonatal calves can depend on the type used, the mode of administration and the environmental status.…”
Section: Faecal Biomarkersmentioning
confidence: 99%